Childhood, Homesickness and the Generation Gap in the Literature of Slovenian Emigrants - Žitnik Serafin, Janja (Two Homelands, 2010)
The author discusses various aspects of childhood and impacts on childhood as they are mirrored in literary works written by sixty Slovenian émigré writers. She is interested in how émigré literature pictured for Slovenian emigrant children themes like childhood in the old country and life in the new homeland, what these children actually experienced within and outside their families in different historical periods of Slovenian emigration, and how all this influenced their world views as well as the typical features of the generation gap in migrant context. The author compares some thematic characteristics of Slovenian émigré literature with similar elements found in the works written by immigrant writers in Slovenia.